Lawfare and legitimacy: The wicked problem of judicial resilience at a time of judicialisation of politics in South Africa - Dent, Kate (Department of Public Law, 2022)
In the period from 2009-2020, South Africa has witnessed the rise of "lawfare". Lawfare is understood as the judicialisation of politics - turning to the courts and the use of the law to resolve broadly political matters. This thesis explores the unfolding implications of the judicialisation of politics for judicial legitimacy. In the displacement of the political into the judicial the reach of the courts is expanded and the legitimacy of courts engaging in a "political" role is questioned. Situated in the field of judicial-political dynamics, the interplay between law and politics is observed through the adoption of a historical-institutionalist model. This thesis identifies the causes of the judicialisation of politics and then traces its consequences for broader constitutional stability and the impact on the judicial institution. Guidelines for the Court to navigate lawfare to achieve institutional resilience and maintain judicial legitimacy are then proposed. Judicialisation of politics is caused primarily through the failures of the other branches of government to fulfil their assigned constitutional role. Institutional imbalance in a dominant party democracy means that opposition parties and civil society organisations are left with little recourse but to appeal to the Court to be a constitutional bulwark. The Court is then compelled to step into the breach and fill the accountability vacuum. In identifying the causes of judicialisation, a fuller understanding of Lawfare emerges, expanding current scholarship beyond its traditionally abusive characterisation. It posits a duality to Lawfare in that it can be both an abuse of law and a last line of defence. Through observing the judicial political interactions, a trajectory from the judicialisation of politics to the politicisation of law is mapped. The politicisation of law sees political power refocused on the courts, exposing them to political aggression and attack by the dominant party. The judicialisation of politics that seeks accountability from recalcitrant political actors asks much of the courts, at a time when ensuring executive oversight is the most dangerous, because of the ease with which a hostile executive in a dominant party democracy can implement measures that may undermine the independence of the judiciary. The Constitutional Court has shown a remarkable ability to navigate this era of Lawfare, remaining resolute under fire. However, the more successful the Court is in holding the line against executive abuse of power, the more the judicial route is identified as a powerful weapon to achieve more abusive political objectives. The relationship between Lawfare and legitimacy is identified as a wicked problem that demands expanding boundaries to observe the courts influence on the political environment, and the political environment's influence on the judicial role and its legitimacy. Through advancing a multi-dimensional paradigm of judicial legitimacy, the dialectics of judicial legitimacy are shown to be aggravated by the judicialisation of politics. In this respect it is argued that where the foundations and assumptions on which legitimacy is predicated shift, legitimacy must be re-examined. It is therefore argued that in a culture marked by an impunified disregard of non-judicial regulatory enforcement and increasing non-compliance with judicial orders, the impulse to preserve legitimacy through a detached, formalist stance will not be sufficient. Judicial legitimacy must be relocated in the ability of the Court to be responsive. Pulled into the role of judicial statesmanship, the Court must adopt a robust approach to assertively uphold the rule of law. In tracking the unfolding consequences of the judicialisation of politics, the Court is asked to resolve matters beyond its institutional capabilities. Absent the normative commitment to the rule of law, the internationalisation of constitutional norms, and the political interest to implement remedial orders, the Court is unable to effect workable relief. In tracing the dangers of the continued trend of Lawfare, the thesis sketches a downward spiral of reputational strength of the Court and a decline in democratic responsibility. This leads to an inability to achieve effective reform that ends in disenchantment, questioning the faith placed in the Constitution. It depicts how the Constitutional Court as 'constitutional saviour' can unravel into constitutional blame. The Constitutional Court has been able to hold the line in this era of Lawfare and repel assaults on its integrity and efforts to undermine its independence. However, without a broader culture of commitment to the rule of law, civil education and a suffusion of constitutional responsibility beyond the judiciary, the Court will not be able to continue to shoulder the weight of what is asked of it. This research depicts a circular model of Lawfare and legitimacy, where Lawfare is predicated on judicial legitimacy, but an overreliance on Lawfare will destroy judicial legitimacy.